Project factsheet: Overcoming barriers to women’s political participation through advocacy training: Designing a field experiment in Nigeria - Adida, Claire; Arriola, Leonardo; Kosec, Katrina; Matanock, Aila; Mo, Cecilia Hyunjung (International Food Policy Research Institute, 2021)
This factsheet describes a planned project in Nigeria, working with existing partners, that will provide useful recommendations for empowering women in the public sphere. It has the potential to inform implementation of the National Gender in Agriculture prepared by the Federal Ministry of Agriculture and Rural Development (FMARD) and programming by the Federal Ministry of Women Affairs and Social Development (MWASD) by sharing specific lessons on how to harness women’s social capital and leadership skills to promote more equitable agricultural and development policies. The project pairs an intervention aimed at generating leadership skills, a sense of collective efficacy, and effective participation in local politics among women’s groups in Nigeria with a rigorous randomized controlled trial (RCT) to understand what works and how to give women a voice in their communities. It builds on programming by ActionAid Nigeria, our implementing partner; we will further refine this programming through qualitative work and embed it in a theory of change. ActionAid Nigeria prioritizes the leadership of women, especially those living in poverty and exclusion.